Sonazoid-Conjugated Natural Killer Cells for Tumor Therapy and Real-Time Visualization by Ultrasound Imaging - Hyeong-Woo Song; Han-Sol Lee; Seok-Jae Kim; Ho Yong Kim; You Hee Choi; Byungjeon Kang; Chang-Sei Kim; Jong-Oh Park; Eunpyo Choi (MDPI AG, 2021)
Various cell therapy strategies, including chimeric antigen receptor-expressing T or natural killer (NK) cells and cell-mediated drug delivery, have been developed for tumor eradication. However, the efficiency of these strategies against solid tumors remains unclear. We hypothesized that real-time control and visualization of therapeutic cells, such as NK cells, would improve their therapeutic efficacy against solid tumors. In this study, we engineered Sonazoid microbubble-conjugated NK (NK_Sona) cells and demonstrated that they were detectable by ultrasound imaging in real-time and maintained their functions. The Sonazoid microbubbles on the cell membrane did not affect the cytotoxicity and viability of the NK cells in vitro. Additionally, the NK_Sona cells could be visualized by ultrasound imaging and inhibited tumor growth in vivo. Taken together, our findings demonstrate the feasibility of this new approach in the use of therapeutic cells, such as NK cells, against solid tumors.